Ideology of National Insight in Teaching Materials of Compulsory Curriculum Subjects of Indonesian Language: Norman Fairclough's Perspective - Zulfadhli, Muhammad; Anshori, Dadang; Sastromiharjo, Andoyo; Minto, Deri Wan; Farokhah, Laely (KEMBARA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2024)
National insight is an important concept that should be internalized by the younger generation. The understanding of national insight among students, as the younger generation, is still categorized as insufficient, so efforts are needed to strengthen national insight through the Compulsory Curriculum Subjects of Indonesian Language. This research aims to reveal the ideology of national insight within the teaching materials of Compulsory Curriculum Subjects of Indonesian Language from Norman Fairclough's perspective in 2013 with the theory of critical discourse analysis. This research used a qualitative approach. The research data were obtained from texts in the teaching materials of Compulsory Curriculum Subjects of Indonesian Language. Texts containing the concept of national insight were analyzed using Norman Fairclough's 2013 model of critical discourse analysis. The research data obtained were analyzed through the stages of reduction, presentation and verification. The data validation in this research was conducted using triangulation techniques. The results showed that in terms of the text aspect, both texts represent the ideology of love for the nation and homeland, as well as the aspiration for a just and prosperous society, through a text theme focusing on the obligation to pay taxes. In terms of discourse practice, the role of language in both texts serves as a tool for promoting an ideology by the involved groups. Furthermore, in terms of social-cultural practice, both texts emphasize socio-economic aspects. In conclusion, the teaching materials of Compulsory Curriculum Subjects of Indonesian Language represent several ideologies of national insight through texts that are presented as a means of spreading ideology by considering social and economic aspects. The results of this research have implications for national insight education for students in higher education through texts containing national insight contained in teaching material of Compulsory Curriculum Subjects of Indonesian Language.